(untitled) (Journal of the College of Basic Education, 2022)
Throughout the literary eras, the subject of “instigation” was present in Arab poetry, but for many political-social reasons it appeared in al-Husayni poetry, especially in the nineteenth century AD. This topic added to poetry an objective-art phenomenon in a number of its poetic purposes such as praise, lament, and enthusiasm, Blame and complaint .., with linguistic methods, including: appeal, interrogation, command, and repetition .., turned from its real purposes to rhetorical purposes according to the poet’s vision and his experience in dealing with his current situation at that time, taking advantage of the historical-religious-ideological heritage of his poetic language and its images with artistic sincerity in expression, description, sobriety of speech, strength of meaning and plumbing of sentences, to which it added to Arab poetry the dialectic of salvation hope and tragic pain in his instigation of Imam al-Mahdi (pbuh) rescued and saved from the oppression of the sultans, especially the Ottoman authority that oppressed the Islamic nation, so the most important poets defend it, including our poets, , Sayyid Haider al-Hilli and Sayyid Ja`far al-Hilli, despite many studies and research in their poetry, but I did not find a research that dealt with the balance between their poemings and instigation, especially that they have lived together in one environment for more than ten years in two cities: Hilla Al-Fayhaa and Najaf Al-Ashraf .. Our research tagged ( The agitation in the poems of Messrs. Haider al-Hilli and Ja`far al-Hilli - Imam al-Mahdi "AJ" as a model ) used the methodology of the objective-stylistic balance between their poems, and according to the limited research, our research did not address all topics of their poems, such as praise, , and lamentation and enthusiasm for Bani Hashem and Hussein.. and others, And it had some important results, the most important of which is that Sayyid Ja`far al-Hilli, has lived as a poet with the life of Sayyid Haider al-Hilli for seventeen years of age, because he (Ja`far) loaned poetry at ten years of age, and that they had participated on the day of their birth, God willing, that the anniversary of Imam Mahdi’s birth in the middle of the month of Sha’ban will be the common denominator for the day of their birth, Haider in its night, and Ja`far during its day, in one city is the “Hilla” to which he is attributed, after the death of the two poets, we were also buried in one city, Najaf al-Ashraf -the estate of their sciences- in the cemetery of Wadi al-Salam. By scheduling the topics of their poems, and the methods used in it, it became clear to the researcher that there is a clear difference in the number of times the poet has addressed these issues and the number of methods used in it, and the extent of its impact on the research methodology, “balancing”, and that Haider Al-Hilli’s wait for Imam Al-Mahdi was a negative wait While Jafar al-Hali was waiting for a positive wait, and Jafar Al-Hali was calling forrevenge for religion and Sharia more than Haider Al-Hali, and in the topic of "seeking revenge", we find that they have resorted to using Verbal improvers And more interrogative tools and Imperative, due to the necessity of the situation and the delay of Revenge on the killers of Muhammad (r), Haider was distinguished from Ja`far for his singularity in using some subjects, and he was more than using linguistic methods .